Knowledge, Attitude, and Practices Related to COVID-19 among Healthcare Personnel in a Tertiary Care Hospital in Nepal: A Cross-sectional Survey - Basnet, S.; Dahal, S.; Tamrakar, D.; Shakya, Y.R.; Jacobson, C.; Shrestha, J.; Shrestha, S.K. (Kathmandu University Medical Journal, 2020)
Background COVID-19 is significantly affecting the healthcare system globally. As a result, healthcare workers need to be updated on the best practices for the proper management of the disease. Objective The purpose of this study was to assess the knowledge, attitude, and practices (KAP) related to COVID-19 among healthcare personnel. Method This was a cross-sectional study conducted among medical personnel at Dhulikhel Hospital Kathmandu University Hospital using a semi-structured questionnaire on KAP related to COVID-19 from May 8th to June 8th, 2020. We analyzed survey data by using descriptive statistics. Spearman rank correlation, chi-square test and binary logistic analysis were used to examine the association between sociodemographic characteristics with KAP related to COVID-19. Result Among 220 participants, the majority were nurses (60%) followed by doctors (27.7%), paramedics (10%) and technicians (2.3%). The results showed that 68.6% of healthcare personnel had a good knowledge with appropriate practices (98.5%) and negative attitude (59.3%). In the multivariate binary logistic analysis, the healthcare workers with the clinical experience level of one to five years (OR:.42, 95% CI:.19- .96) and more than 5 years (OR: .16, 95% CI: .04-.63) were significantly associated with negative attitude. The confidence score for managing COVID-19 (OR:1.16, 95% CI:1.02-1.34) was significantly associated with an optimistic attitude. Conclusion Healthcare workers are knowledgeable about COVID-19 and proactively practising to minimize the spread of infection but lack optimistic attitudes. Hence, the constantly updated educational programmes related to COVID-19 for targeted groups will contribute to improving healthcare workers’ attitude and practices.